GEOCHEMICAL AND SCLEROCHRONOLOGICAL ANALYSES OF THE LOWER PLEISTOCENE MACROFAUNA OF WESTERN EMILIA (NORTHERN ITALY): PALAEOENVIRONMENTAL AND PALAEOCLIMATIC IMPLICATIONS ... - CRIPPA, GAIA (Universit degli Studi di Milano, 2015)
The Early Pleistocene is a time interval characterized by several climatic oscillations which has its lower and upper boundaries coinciding respectively with the beginning of the Northern Hemisphere Glaciation and the Middle Pleistocene Transition. The Mediterranean area was strongly affected by the Early Pleistocene climatic changes. One of the most important biotic event is here represented by the appearance of the boreal guests (e.g. the bivalve Arctica islandica and the foraminifer Hyalinea balthica) at the beginning of the Calabrian Stage, suggesting significant cooling of the Mediterranean Sea, which is also confirmed by a change in the pollen flora indicating cold climatic conditions. The Arda River marine succession, cropping out in Western Emilia, Northern Italy, is very rich in macrofossils and it covers without significant gaps the Early Pleistocene. It thus represents an ideal setting where to study the climatic oscillations of this time interval. This study, combining sedimentology, taxonomy, ...